Armenian toponyms based on plant-names in the province of Syunik - Martirosyan, Hrach; Aramyan, Anna (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
From the earliest records to the modern period, Armenians have formed the main ethnic population of Syunik (Siwnik‘, cf. Jage/ajor and its Turkified form Zangezur), Artsakh (Arc‘ax [Karabakh / Gharabagh]), and, to a lesser extent, Utik. This is well attested by Classical Armenian sources from the 5th century, the abundance of Armenian place names, and by non-Armenian authors such as Ptolemy and Strabo. Additional evidence includes architectural monuments, xač‘k‘ars (cross-stones), inscriptions, manuscript colophons, and more. According to the 7th-century Ašxarhac‘oyc‘, Syunik and Artsakh are the ninth and tenth provinces of Greater Armenia. In the 8th century, Stepannos Syunetsi listed Siwni and Arc‘axayin among the ‘seven marginal dialects’ (zbaṙsn zezerakans). This body of evidence refutes the Azerbaijani academic and political narrative that denies the Armenian historical presence in these regions and seeks to rebrand Syunik as ‘Western Azerbaijan’. Such claims aim to legitimize acts of war, forced displacement, and occupation, and reflect a broader policy of Armenophobia and cultural erasure. This paper applies a linguistic approach to the issue, focusing on dialectal continuity in Syunik and Artsakh. It examines toponyms derived from plant designations, typically formed with suffixes such as -eni, -eak / -(u)k, -i, -ut, -e(a)n, and -k‘, and occasionally components like t‘aɫ ‘quarter’ and mayri ‘forest’. The main source is the ‘tax of the 12 regions of Syunik’ from Step‘annos Ōrbelean’s History of Syunik. Many of the toponyms discussed here are based on word forms that reflect phonological developments characteristic of the Syunik-Artsakh dialectal region, or that include lexical items specific to this area. At the same time, the plant-derived nature of these place names points to a deep connection between the natural landscape and the communities inhabiting it. Together, these linguistic and ecological factors provide strong evidence for the continuous and centuries-long presence of the Armenian language in this region.